2022
DOI: 10.3390/ijerph191912506
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Physical Activity for Informal Caregivers during and beyond COVID-19: Exploring the Feasibility, Usability and Acceptability of a Digital Health Smartphone Application, ‘CareFit’

Abstract: The COVID-19 pandemic has exposed how our global societies rely upon the care and support of informal (unpaid) caregivers: in the UK alone, there are an estimated 6.5 million informal carers. The caring role is not just precarious, it is often associated with high levels of stress, poor/deteriorating health and crisis points (hospitalisations, worsening of health). Fittingly, there has been much research in recent years focusing on mental health supports. A lesser explored area is physical health and physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This result is not surprising because the informal caregivers expressed a strong interest in technological innovations to support them in their caregiving role [26]. Despite this finding, only a third of our respondents had ever used an application for physical activity, although a recent study demonstrated the feasibility, usability, and acceptability of novel digital health apps for informal caregivers to improve their physical activity levels [51].…”
Section: Discussionmentioning
confidence: 76%
“…This result is not surprising because the informal caregivers expressed a strong interest in technological innovations to support them in their caregiving role [26]. Despite this finding, only a third of our respondents had ever used an application for physical activity, although a recent study demonstrated the feasibility, usability, and acceptability of novel digital health apps for informal caregivers to improve their physical activity levels [51].…”
Section: Discussionmentioning
confidence: 76%